Opening the reserves floodgates: The SARB's new excess reserve system and its impact on the South African banking system - Ekstein, Joe Donald (Department of Finance and Tax, 2025)
This research evaluates the impact on the South African banking system of the South African Reserve Bank's (SARB) decision to shift from the traditional shortage reserves system to one that is now based on excess reserves. This shift changes the behaviour of the banking system that could have significant implications for the South African economy, especially for credit extension. This research focuses on three main questions. First, has there been a significant increase in reserves observed in the South African banking system since the shift to an excess reserves system? Second, has there been any notable changes in the interbank lending market since the shift to an excess reserves system? Third, has there been any notable changes in credit extension to the South African domestic economy since the shift to an excess reserves system? To answer these questions, this research used descriptive statistics to evaluate the significance of the shift to an excess reserves system while a Threshold Autoregressive (TAR) Model was used to evaluate the dynamics between excess reserves, the Jibar-repo spread and credit extension to the domestic economy. The research comprises of monthly time-series data from the period January 2000 up to August 2024. This research finds that there has been a significant increase in the level of excess reserves in the South African banking system and the estimation results show that spreads in the interbank market and credit extension display regime-specific behaviour relative to excess reserves. There is an inverse relationship among the variables in a declining reserves regime and conversely, a direct relationship among the variables in an increasing excess reserves regime. The implications of these findings are important in understanding the role the SARB now plays in the South African banking system as a risk-free borrower that competes with others in the financial system for banks' surplus funds. Given the recency of this shift, this research contributes to the existing body of knowledge in two primary aspects. First, it studies the shift from a shortage reserve system to an excess reserve system in an emerging-market context such as South Africa where most research on this topic focuses on developed markets. Second, the shift of the SARB to an excess reserve system is recent and not yet well understood and this research contributes to that understanding and paves the way for further empirical research as more data becomes available.